IMPLEMENTASI TOTAL QUALITY MANAJEMEN (TQM) DI SMP ATHIRAH 1 MAKASSAR - Novita Novita Novita (Jurnal Teknologi Pendidikan Madrasah, 2019)
To achieve the nation's progress, Indonesia needs quality human resources, because our nation will not be able to compete with other countries without having quality resources. the main function of education is to prepare students (the next generation) with the abilities and skills needed to have the ability and readiness to plunge into the community (environment). Education is a strategic means to improve the quality of a nation, because the progress of a nation can be measured by the progress of its education. This study aims to determine the implementation of TQM in Athirah 1 Islamic Middle School in Makassar. The type of research used is Qualitative with data collection techniques, namely: data collection observation, interviews, and documentation. The implementation of TQM in Athirah 1 Islamic Middle School in Makassar still requires real evidence in the form of Accreditation Value and religious application of each student that is not only focused on science and technology in accordance with the Vision of Makassar 1 Athirah Islamic Middle School.